2005
DOI: 10.1074/jbc.m413988200
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Inhibition of Protein Aggregation and Precipitation by Transglutaminase-catalyzed Intermolecular Cross-linking

Abstract: Cross-linking of proteins catalyzed by tissue transglutaminase has been suggested to play key roles in a variety of cellular events, including cell apoptosis and human pathogenesis (e.g. polyglutamine and Alzheimer diseases). It has often been suggested that tissue transglutaminase enhances aggregation and precipitation of damaged or pathogenic proteins. To ascertain whether this is accurate, we investigated the effects of tissue transglutaminase-catalyzed modulation on the aggregation of structurally damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…At physiological conditions inside neurons, a-synuclein concentration is estimated to be 70 to 140 mM (Lodish 2000;Schults 2006), while the neuronal tTG concentration has been reported to be in the nanomolar range (Konno et al 2005b). Thus intramolecularly cross-linked a-synuclein is likely the main reaction product of tTG cross-linking in vivo, consistent with the observation of highly enriched intramolecularly cross-linked a-synuclein monomers together with a small fraction of oligomers in PD substantia nigra compared to control tissue (Andringa et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At physiological conditions inside neurons, a-synuclein concentration is estimated to be 70 to 140 mM (Lodish 2000;Schults 2006), while the neuronal tTG concentration has been reported to be in the nanomolar range (Konno et al 2005b). Thus intramolecularly cross-linked a-synuclein is likely the main reaction product of tTG cross-linking in vivo, consistent with the observation of highly enriched intramolecularly cross-linked a-synuclein monomers together with a small fraction of oligomers in PD substantia nigra compared to control tissue (Andringa et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to an earlier report (Konno et al 2005a) using micromolar tTG concentrations, we explored the effect of nanomolar tTG concentrations, consistent with cellular tTG levels, on a-synuclein cross-linking (Murtaugh et al 1984;Konno et al 2005b). SDS-PAGE ( Fig.…”
Section: Ttg Concentration-dependent Cross-linking Of A-synucleinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although all these studies suggest the possible involvement of the TGs in the formation of deposits of protein aggregates in neurodegenerative diseases, they do not indicate whether aberrant TG activity per se directly determines the disease progression. For example, several experimental findings reported that TG2 activity in vitro leads to the formation of soluble aggregates of a-synuclein [47] or polyQ proteins [48,49] . To date, as previously reported, at least ten human CAG-expansion diseases have been described (Table 2) [50][51][52][53][54][55][56][57][58][59] and in at least eight of them their neuropathology is caused by the expansion in the number of residues in the polyglutamine domain to a value beyond [35][36][37][38][39][40].…”
Section: Role Of the Transglutaminases In Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, although all these studies suggest the possible involvement of the TGs in the formation of deposits of protein aggregates in neurodegenerative diseases, they do not indicate whether aberrant TG activity per se directly determines the disease progression. For example, several experimental findings reported that TG2 activity in vitro leads to the formation of soluble aggregates of a-synuclein [47] or polyQ proteins [48,49] . To date, as previously reported, at least ten human CAG-expansion diseases have been described (Table 2) [50][51][52][53][54][55][56][57][58][59] and in at least eight of them their neuropathology is caused by the expansion in the number of residues in the polyglutamine domain to a value beyond 35-40.…”
Section: P O S S I B L E R O L E S O F T H E T R a N S G L U T A M I mentioning
confidence: 99%